O szczególnym wymiarze żydowskiej tożsamości - Grosfeld, Jan (Człowiek i Społeczeństwo, 2012)
This essay tries to present a special face of the Jewish people in the history of man and world. As a key to understand the Jewish condition and identity I am using a well known notion of “the wandering Jew”. The counterpoint to a negative perception of this idea of Jews is a deep and real insight in their identity. This identity was shaped through the exceptional, consecutive encounters of Hebrews, Israelis, of the Jewish people with the unique God. He is unique also by the fact of their election and guidance on the way aiming to experience Him as the Lord full of love to them. This “knowing” of God occurs through the mutual relations between people and peoples. The fundamental feature of the Jewish condition is wandering, un-domestication which should result in breaking with these fetters and ties which make impossible our self-understanding which is a condition of a veritable freedom. This freedom is recognized in fulfilling one’ s vocation which starts with the election by God. The patriarchs of Israel – Abraham, Isaac and Jacob are the figures-icons useful in a better existential understanding of man and God. The Shoah which was so terrifying tragedy of Jews was a turning point for the Jewish reflection on their own vicissitudes, on the relation to God and the whole history. In the same time the Shoah was and should be fundamental to the contemporary civilization as well as to Christians and Churches in perceiving their vocation and mission.